THE ROLE FAIRY TALE IN SOCIALIZATION OF ELDER PRESCHOOL CHILDREN - Yusupova, Muhabbar (Журнал иностранных языков и лингвистики, 2021)
Ideas and knowledge about the world around them are more easily perceived by children if they are presented in the form of games, travels and fairy tales. Fairy tales are capable of giving children an idea of the world around them in an entertaining way, better understanding and understanding it. Fairy-tale forms of perception help to introduce an unusual situation into the studied material, thereby reviving it. With the help of fairy-tale images, teachers find approaches to disclosing the emotional spheres of children. Children listen to fairy tales, learn to worry about heroes, solve seemingly difficult tasks, learn to reason, give reasons for their actions and build logical chains.